2021
DOI: 10.1093/bib/bbab330
|View full text |Cite
|
Sign up to set email alerts
|

Functional meta-omics provide critical insights into long- and short-read assemblies

Abstract: Real-world evaluations of metagenomic reconstructions are challenged by distinguishing reconstruction artifacts from genes and proteins present in situ. Here, we evaluate short-read-only, long-read-only and hybrid assembly approaches on four different metagenomic samples of varying complexity. We demonstrate how different assembly approaches affect gene and protein inference, which is particularly relevant for downstream functional analyses. For a human gut microbiome sample, we use complementary metatranscrip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In this study, we report how lower than recommended DNA input affects Nanopore long-read metagenomics by comparing different levels of metagenomic analysis from read QC to retrieval of MAGs. Many previously published Nanopore-based metagenomics studies lack information about the quantity of DNA used for library preparation [19,[24][25][26]32]. To the best of our knowledge, other published metagenomic studies quantified the amount of input DNA and met or exceeded the recommended amount of 1000 ng DNA for input material.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report how lower than recommended DNA input affects Nanopore long-read metagenomics by comparing different levels of metagenomic analysis from read QC to retrieval of MAGs. Many previously published Nanopore-based metagenomics studies lack information about the quantity of DNA used for library preparation [19,[24][25][26]32]. To the best of our knowledge, other published metagenomic studies quantified the amount of input DNA and met or exceeded the recommended amount of 1000 ng DNA for input material.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al (2021) used resistome risk score based on co-occurrences of ARGs, MGEs and pathogen gene markers on the same contig to evaluate convergence of biological output produced by different assemblers. Another paper by Galata et al (2021) showed that the choices of assembly software as well as sample complexity have considerable impact on prediction of genes and proteins. A recent study by Yorki et al (2023) focused on assessment of short-, long- and hybrid-approaches to recover the genome of clinically relevant low-abundant E. coli and their ARG content from metagenomic samples.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report how lower than recommended DNA input affects Nanopore long-read metagenomics by comparing different levels of metagenomic analysis from read QC to retrieval of MAGs. Many previously published Nanopore-based metagenomics studies lack information about the quantity of DNA used for library preparation [ 19 , 24 26 , 32 ]. To the best of our knowledge, other published metagenomic studies quantified the amount of input DNA and met or exceeded the recommended amount of 1000 ng DNA for input material.…”
Section: Discussionmentioning
confidence: 99%